PELATIHAN PEMBUATAN LAPORAN KEUANGAN PERUSAHAAN DAGANG DENGAN MENGGUNAKAN APLIKASI ACCURATE BAGI SISWA-SISWI KELAS XII SMK PGRI 1 PRABUMULIH - Bayu Dharmaraga Alkahfi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
This service aims to provide training in the creation of financial statements for trading companies using Accurate version 4 software to students in the twelfth grade of SMK PGRI 1 Prabumulih. Accurate version 4 is accounting software that can enhance efficiency in financial statement management. In the context of the Merdeka Curriculum, this service supports the development of skills and knowledge relevant to an increasingly competitive job market.Through a series of practical training sessions, students will be taught how to use Accurate version 4 to record financial transactions, generate financial statements, and conduct financial data analysis for companies. This training will provide a deep understanding of the pivotal role of financial statements in informational business decision-making.The outcomes of this service are expected to bring tangible benefits to students at SMK PGRI 1 Prabumulih, enhancing their skills in managing financial statements using cutting-edge technology. This will better prepare them to face challenges in an ever-evolving job market and enable them to contribute more effectively to the industrial world. Additionally, this service is expected to improve students' understanding of the concept of the Digital Era 4.0 and how information technology plays a pivotal role in today's business environment.